Conversion of Tumors into Autologous Vaccines by Intratumoral Injection of α-Gal Glycolipids that Induce Anti-Gal/α-Gal Epitope Interaction - Uri Galili (Clinical and Developmental Immunology)
Anti-Gal is the most abundant antibody in humans, constituting 1% of immunoglobulins. Anti-Gal binds specifically α-gal epitopes (Galα1-3Galβ1-4GlcNAc-R). Immunogenicity of autologous tumor associated antigens (TAA) is greatly increased by manipulating tumor cells to express α-gal epitopes and bind anti-Gal. Glycolipids with αgal epitopes (α-gal glycolipids) injected into tumors insert into the tumor cell membrane. Anti-Gal binding to the multiple α-gal epitopes de novo presented on the tumor cells results in targeting of these cells to APC via the interaction between the Fc portion of the bound anti-Gal and Fcγ; receptors on APC. The APC process and present immunogenic TAA peptides and thus, effectively activate tumor specific CD4+ helper T cells and CD8+ cytotoxic T cells which destroy tumor cells in micrometastases. The induced immune response is potent enough to overcome immunosuppression by Treg cells. A phase I clinical trial indicated that α-gal glycolipid treatment has no adverse effects. In addition to achieving destruction of micrometastases in cancer patients with advance disease, α-gal glycolipid treatment may be effective as neo-adjuvant immunotherapy. Injection of α-gal glycolipids into primary tumors few weeks prior to resection can induce a protective immune response capable of destroying micrometastases expressing autologous TAA, long after primary tumor resection.